Description of the adult male elongate hemlock scale, Fiorinia externa Ferris (Coccoidea: Diaspididae), with notes on the seasonal development of the species on eastern hemlock, Tsuga canadensis (L.) Carrieré (Pinaceae), in the southern Appalachian region (U.S.A.) - Lambdin, Paris; Hodgson, Christopher; Grant, Jerome (Zootaxa, 2007)
The adult male of Fiorinia externa Ferris is described for the first time. Its morphology agrees with that of previously described adult males in the tribe Diaspidini, and suggests a close affinity to Pseudaulacaspis. F. externa has two complete overlapping generations per year on the needles of eastern hemlock, Tsuga canadensis (L.) Carrieré, in the eastern Tennessee (USA) southern Appalachians. Adult females (both gravid and non-gravid) and first-instar nymphs were the dominant overwintering stages, although all stages apart from the adult males were present throughout the winter months. Adult males began emerging in mid March with emergence peaks in mid April to early May and again in mid to late September.